2021
DOI: 10.2147/cmar.s299827
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Robotic Single-Site Surgery and Laparoendoscopic Single-Site Surgery as Therapeutic Options for Stage IB1 Cervical Squamous Carcinoma

Abstract: Purpose To compare perioperative outcomes between robotic single-site surgical technique and conventional laparoendoscopic single-site surgical technique. Methods This was a retrospective cohort study involving 67 patients who received robotic single-site surgery or laparoendoscopic single-site surgery for the treatment of stage IB1 cervical squamous carcinoma. The robotic single-site radical hysterectomy technique combined with pelvic lymph node dissections were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…We found that the use of TU-LESS resulted in enhanced recovery for our patients; the surgical outcomes were also consistent with those of previous studies [24][25][26]. The rate of postoperative complications were slight higher than previous TU-LESS reports, since most reports focused on the benign lesions or others which focused on malignant disease with small sample size (2.7%-8.5%) [24,27,28]. Fagotti et al reported that with endometrial cancer surgery, the median operation time was 129 minutes, ranging from 45 to 321 minutes, and that estimated blood loss was 70 mL, ranging from 10 to 500 mL-since the majority of patients did not undergo lymphadenectomy.…”
Section: Interpretation (In Light Of Other Evidence)supporting
confidence: 91%
See 1 more Smart Citation
“…We found that the use of TU-LESS resulted in enhanced recovery for our patients; the surgical outcomes were also consistent with those of previous studies [24][25][26]. The rate of postoperative complications were slight higher than previous TU-LESS reports, since most reports focused on the benign lesions or others which focused on malignant disease with small sample size (2.7%-8.5%) [24,27,28]. Fagotti et al reported that with endometrial cancer surgery, the median operation time was 129 minutes, ranging from 45 to 321 minutes, and that estimated blood loss was 70 mL, ranging from 10 to 500 mL-since the majority of patients did not undergo lymphadenectomy.…”
Section: Interpretation (In Light Of Other Evidence)supporting
confidence: 91%
“…We found that the use of TU-LESS resulted in enhanced recovery for our patients; the surgical outcomes were also consistent with those of previous studies [24][25][26]. The rate of postoperative complications were slight higher than previous TU-LESS reports, since most reports focused on the benign lesions or others which focused on malignant disease with small sample size (2.7%-8.5%) [24,27,28].…”
Section: Interpretation (In Light Of Other Evidence)supporting
confidence: 90%
“…In a study spanning various surgical specialties, laparoscopic procedures have been associated with reduced operating costs [8]. Similar studies have found improved total operating time and complication rates with a laparoscopic approach [9,10]. Research favoring a robotic approach has noted a decreased length of stay with this intervention [9].…”
Section: Introductionmentioning
confidence: 96%
“…Minimally invasive surgery (MIS) for early-stage cervical cancer undergoes progressive development and acceptance since assimilation of robotic technology into gynecologic cancer surgery in 2005. Patients undergoing robotic surgery have lesser operative complications, reduced estimated blood loss (EBL) and shorter postoperative hospital stay (POHS) [1][2][3][4]. From 3-robotic arm [2,5] to adding the 4th robotic arm [6], attempts have been made to re ne the practicality of robotic platform in surgery for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%